(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article presents the development of a wear complex for leather, prepared using acrylic primer compositions containing alkylcarbonyl ethanolates for chrome leather coating. The study investigates the ability of the AK-224 emulsion preparation to provide the main quality indicator of film-forming agents when used for chrome leather coating.